The Effect of Online vs. Offline Flipped Instruction on EFL Learners' Writing Ability - Rahimi, Ali; Hasheminasab, Morteza (Beyond Words, 2020)
This study aimed at examining the effectiveness of computer-assisted flipped instruction on the writing ability of upper-intermediate Iranian EFL learners and their attitudes toward it. A mixed-method approach was used. A quantitative method employing the quasi-experimental pretest-posttest design was used. Twenty participants were selected based on convenient sampling method and were divided into an online flipped instruction group (N= 10) and an offline flipped instruction group (N= 10). A paired sample t-test and independent samples t-test was used to analyze the obtained data. The results showed that the learners who received online flipped instruction outperformed those who received offline flipped instruction, regarding their performance on the posttest. Based on the findings of this study, it was argued that the learners in the online group had a positive attitude toward this method.